Using GPS wearable technology for performance enhancement in football at premier levels in Zimbabwe - Kamanga, Kudakwashe B. (BUSE, 2024)
Wearable technology has gained significant popularity in the world of sports, especially in football. It offers real-time information and insights that can significantly enhance performance, training, and injury prevention. This research aims to explore how wearable microsensor technology can be used to improve football play at top levels of Zimbabwean football competitions. A mixed method research approach was employed as the chosen research design. The study focused on players, technical and coaching teams from two premier level football teams. Data was collected from the field area through interviews, questionnaires, and tests. Data analysis was done using SPSS for quantitative data and Nvivo 12 for qualitative data. The study's findings suggest that wearable technology has a significant impact on decision-making and technical analysis in premier level football. 30 questionnaires and interviews with a 93.3% response rate were used to collect data. The study's results show that a notable portion of participants (39.29%) used iPads to track player performance through GPS technology. Results indicate that GPS technology can effectively track and analyse player movement patterns during training sessions and matches. Findings from both the questionnaire and interviews indicate that the utilisation of technology in premier-level football to enhance player performance and monitoring is a multifaceted and constantly evolving topic. Wearable devices can aid in the rehabilitation process by monitoring players' progress, tracking recovery metrics, and facilitating a safe return to play after injuries.
Keywords: Wearable technologies; Football; Zimbabwe